Worm-like FeS2/TiO2 Nanotubes for Photoelectrocatalytic Reduction of CO2 to Methanol under Visible Light - Han, E.; Hu, F.; Zhang, S.; Luan, B.; Li, P.; Sun, Hongqi; Wang, Shaobin (American Chemical Society, 2018)
Photoelectrocatalytic (PEC) reduction of CO 2 to hydrocarbons provides a great technique for CO 2 utilization, renewable energy transformation, and storage. Iron disulfide (FeS 2 ), as an earth-abundant and nontoxic semiconductor, has narrow band gap energy, high photovoltaic conversion efficiency, and light absorption, making it very promising as a photoelectrode in a PEC cell. Herein, novel worm-like FeS 2 /TiO 2 nanotubes (NTs) was prepared by introducing FeS 2 on TiO 2 NTs and exhibited excellent PEC performance for CO 2 reduction to methanol. X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and high-resolution transmission electron microscopy (HRTEM) showed that worm-like FeS 2 was densely packed on the TiO 2 NT substrate. By introduction of FeS 2 on TiO 2 NTs, the visible light absorption was improved greatly and the energy band gap energy was narrowed to 1.70 eV, which significantly enhanced the photocatalytic performance under visible light. Furthermore, the resistance was reduced with increasing electrocatalytic ability. The major product of PEC reduction of CO 2 was methanol, reaching 91.7 Î¼mol h -1 L -1 .